Analysis Of Behavior Determinant Factors In Stunting Incidence In Bandung City – Retrospective 2022 - Lolan, Yosef Pandai; Sinaga, Yakobus De Yung (Sean Institute, 2022)
The number of toddlers suffering from stunting in the city of Bandung increased in percentage in 2020 because the number of toddlers measured has decreased due to limited mobility during the COVID-19 pandemic. in 2020, the city of Bandung experienced an increase in stunting rates of 2.40% compared to 2019 with 9,567 toddlers identified as experiencing stunting, in 2021 this fell to 7,568 toddlers. The study aimed to analyze the behavioral determinants of stunting. The research method used is an observational analytic study with a case-control design to see behavioral determinants' influence on stunting. The determinants of this behavior were studied using a retrospective approach, and this research was conducted in the city of Bandung, West Java province. The population in this study was divided into two namely, Case Population and Control Population. The results showed several variables related to the incidence of stunting in the city of Bandung, such as education level (p-value = 0.003; OR = 0.951), local food processing (p-value = 0.014; OR = 0.943), parental knowledge (p-value = 0.006; OR = 0.977), the role of health workers (p-value = 0.005; OR = 0.980), husband's support, (p-value = 0.013; OR = 0.642) and the most dominant variable in this study was husband's support with a p-value of 0.007 and OR 1.929. Conclusion: The risk factors for stunting in toddlers are education level, local food processing, parental knowledge, the role of health workers, and the husband's support. The factor most related to the incidence of stunting is the husband's support.